2001
DOI: 10.1177/00912700122010627
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Gender Differences and Large Intrasubject Variability in Cytochrome P450 Activity Measured by Phenotyping with Dextromethorphan

Abstract: Gender-based differences in cytochrome P450 (CYP) activity may occur due to endogenous hormonal fluctuations with the menstrual cycle, which are altered by oral contraceptives. This study assessed the average activity and within-subject variability in CYP3A4 and CYP2D6 in men, women taking Triphasil, and regularly menstruating women not receiving oral contraceptives. Thirty-three healthy volunteers participated in this 28-day pilot study (12 women receiving Triphasil) (OCs), 11 regularly menstruating women not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
37
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 41 publications
(62 reference statements)
6
37
0
Order By: Relevance
“…The main enzymes responsible for ebastine metabolism, CYP3A and CYP2J2, are present in intestine [7,26,27], where their activity could be contributing to the first pass metabolism of ebastine and to the large interindividual variability observed [7]. Our findings indicated that urine excretion of the CYP3A-generated metabolite, desalkylebastine, displayed a three-fold higher variability than that of carebastine, which is consistent with the large variation observed in the urinary excretion of other substrates metabolized by CYP3A [29,30].…”
Section: Discussionsupporting
confidence: 84%
“…The main enzymes responsible for ebastine metabolism, CYP3A and CYP2J2, are present in intestine [7,26,27], where their activity could be contributing to the first pass metabolism of ebastine and to the large interindividual variability observed [7]. Our findings indicated that urine excretion of the CYP3A-generated metabolite, desalkylebastine, displayed a three-fold higher variability than that of carebastine, which is consistent with the large variation observed in the urinary excretion of other substrates metabolized by CYP3A [29,30].…”
Section: Discussionsupporting
confidence: 84%
“…Some studies have shown that CYP3A4 activity is higher in women than in men (Harris et al, 1995), but others described no major gender-specific differences in CYP3A activity (McCune et al, 2001;Meibohm et al, 2002). To explain the gender differences in the CYP3A4-luc transgene expression in transgenic mice, we speculate that androgen response element (ARE)-like sequences existing in the 5Ј flanking region of CYP3A4 gene may be functionally activated by androgens in mice, but not in humans.…”
Section: Regulation Of Human Cyp3a4 By Xenobiotics In Transgenic Micementioning
confidence: 84%
“…The total urinary recovery of 4 -hydroxymephenytoin in 0-6 h urine was used as the phenotypic measure of CYP2C19 activity [27]. The activity of CYP2D6 was accessed by the dextromethorphan urinary metabolic ratio, calculated as the ratio of amount of dextromethorphan to dextrorphan recovered in 0-6 h urine [28][29][30].…”
Section: Discussionmentioning
confidence: 99%